A Brief Interview to Detect Panic Attacks and Panic Disorder in Emergency Department Patients with Cardiopulmonary Complaints. Issue 1 (January 2018) - SUNG, SHARON C.; RUSH, A. JOHN; EARNEST, ARUL; LIM, LESLIE E.C.; PEK, MAEVE P.P.; CHOI, JOEN M.F.; NG, MAGDALENE P.K.; ONG, MARCUS E.H.
Abstract : Objectives: Patients with panic-related anxiety often initially present to the emergency department (ED) complaining of respiratory or cardiac symptoms, but rates of detection of panic symptoms by ED physicians remain low. This study was undertaken to evaluate the relevance of panic attacks and panic disorder in ED patients who present with cardiopulmonary symptoms and to determine whether a brief symptom-based tool could be constructed to assist in rapid recognition of panic-related anxiety in the ED setting. Materials and Methods: English-speaking adult ED patients with a chief complaint of palpitations, chest pain, dizziness, or difficulty breathing were evaluated for the presence of panic attacks and panic disorder with the Structured Clinical Interview for DSM-IV Axis I Disorders. Participants completed self-report measures to assess panic-related symptoms, comorbid psychiatric conditions, health-related disability, and health service use. Results: In this sample (N=200), 23.5% had panic attacks and 23.0% had panic disorder. Both groups reported higher rates of panic attack symptoms, greater psychiatric comorbidity, greater health-related disability, and higher rates of ED and mental health service use compared with those without either condition. A brief 7-item tool consisting of panic symptoms identified patients with panic attacks or panic disorder with 85% accuracy (area under the curve=0.90, sensitivity=82%, specificity=88%). Conclusions: Patients with panic attacks or panic disorder commonly present to the ED, but often go unrecognized. A brief 7-item clinician rating scale accurately identifies these patients among those ED patients presenting with cardiopulmonary complaints.